Five microsatellite loci for preliminary kinship analysis and implications for conservation in Sumatran Tigers (Panthera tigris sumatrae) - IKRIMA ASRORI; WILSON NOVARINO; DJONG HON TJONG; PATRICK FLAGGELLATA; YOLI ZULFANEDI; DEWI IMELDA ROESMA (Society for Indonesian Biodiversity, 2026)
Abstract. Asrori I, Novarino W, Tjong DH, Flaggellata P, Zulfanedi Y, Roesma DI. 2026. Five microsatellite loci for preliminary kinship analysis and implications for conservation in Sumatran Tigers (Panthera tigris sumatrae). Biodiversitas 27 (5): d270533. https://doi.org/10.13057/biodiv/d270533. Microsatellite markers are widely used in wildlife pedigree analysis due to their high polymorphism and ability to assist in the determination of kinship relationships. Accurate pedigree information is crucial for effective population management and prevention of inbreeding in Sumatran tigers (Panthera tigris sumatrae), particularly in captive breeding programs. Fifteen microsatellite loci in the Felidae family were selected from previous studies and tested in 20 individuals, including six individuals with known kinship relationships, to identify informative and reliable markers for kinship analysis of Sumatran tigers. Amplification results showed that nine loci were consistently amplified in all samples with relatively high polymorphism. These loci were then evaluated for the number of alleles (Na), observed heterozygosity (Ho), polymorphic information content (PIC), amplification consistency, and genotyping error rate. Five loci showed consistent amplification and high levels of heterozygosity and polymorphism, with three loci (FCA279, FCA304, and FCA391) showing an error rate of 0.00, while two loci (FCA441 and 6HDZ700) had a lower error rate. Therefore, these five loci were selected as candidate markers for the Sumatran tiger pedigree analysis. Meanwhile, the other four loci (FCA008, 6HDZ463, 6HDZ170, and FCA220), although showing high Na, Ho, and He values, also had high error rates. Therefore, these four loci were excluded from further analysis. Cumulative probability of identity (PID) and PIDsibs estimates indicated that the selected panel of five loci had greater discriminatory power than only three loci. Kinship analysis using the selected loci yielded the expected relationships among known individuals, although the software's analysis model does not explicitly define parent-offspring relationships. Therefore, these results are preliminary and require further validation before broader application, given the limited sample size and incomplete representation of pedigree relationships.